The effect of nitrification on fixed 15N ammonium release in soil - David STOPAR; Ivan MAHNE; France MEGUŠAR (Acta Agriculturae Slovenica)
Effect of nitrification on defixation of clay fixed ammonium was studied in soil with pronounced ammonium fixing capacity. Soil samples were amended with 15N labeled ammonium. Significant part of added ammonium (50–70 %) was not exchangeable with 2N KCl after the first 10 minutes of incubation. Dynamics of 15N in 2N KCl exchangeable mineral nitrogen was followed during 28 days of aerobic and anaerobic incubation. Exchangeable ammonium was microbialy converted to nitrite and nitrate during aerobic incubation. When the exchangeable ammonium pool was empty, a slow defixation of chemically fixed ammonium occurred. Approximately 20 % of additionally fixed ammonium was released in the second half of aerobic incubation. No defixation occurred during anaerobic incubation.